Pelatihan Pemanfaatan Internet Bagi Remaja Karang Taruna RW. 05 Cipedak Jagakarsa Jakarta Selatan - Hidayat, Syamsu; Aliftian, Muhammad; Rhama, Muhammad (Jurnal Pengabdian Teratai, 2020)
During this time of the Covid-19 corona virus pandemic, we are required to continue to work and carry out strict health protocols to reduce the rate of spread of this virus. The current advancement of internet technology, especially in big cities like Jakarta, can answer the challenge where we can work from home and learn from home by using an internet connection. There are already many platforms available to minimize face-to-face meetings. Not everyone, especially youth organizations, fully understands the use of the internet. That the benefits obtained from the internet can add knowledge and improve the economy, including learning through available online sites, as well as online sites and applications that make it easier for people to transact online. Opening his way of thinking how to manage and utilize internet functions optimally. Synergy between campuses and regional administrators is needed to support an activity to increase the ability of youth to use the internet. the development and need for the Internet of Things (IOT), thus giving rise to various innovations in meeting the needs of life. as well as getting the benefits of making attractive videos uploaded on YouTube. even some national celebrities are expanding by making several videos uploaded to get paid from advertisements on youtube. The world is running too fast, so we have to adapt quickly, by utilizing the internet optimally.